Comparison of Carcass Percentage Among Four Duck Breeds under Traditional Rearing Conditions - Hafid, Harapin (Talenta Publisher, 2024)
The research aims to determine the extent of differences in the carcass composition of four types of ducks using semi-intensive cultivation. A total of 16 ducks aged 3 months were used as experimental units. A completely randomized design with 4 treatments and 4 replications was the research design. The results showed that ducks of the same age, namely: Alabio ducks, Peking ducks, Mojosari ducks, and Manila ducks, showed very significant differences (P<0.01) in the variables of slaughter weight, carcass percentage, thigh and back percentage. However, there was no significant difference (P>0.05) in the percentage of chest, wings, and neck. It was concluded that the live weight, carcass percentage, and carcass parts of Manila ducks were higher than those of Alabio, Peking, and Mojosari ducks. Meanwhile, Alabio ducks are taller than Peking ducks and Mojosari ducks.